TREC-Lebanon – rapid tranquilisation of patients at risk of an aggressive episode in the emergency psychiatry setting - Dib, Joseph (2020)
Violent or aggressive episodes are particularly prevalent in the emergency psychiatric settings (10%) often as a consequence to a variety of disorders ranging from the organic to mental disorders (i.e. Schizophrenia, Substance Use, etc.). While guidelines state patients should be calm in order to attain a diagnostic history, physical and laboratory tests before treatment is to be started, the violent episode presented often makes it impossible – ruining necessary history, physical and laboratory work as well as placing both staff and patients in a potentially harmful state. With this, rapid tranquilisation becomes both necessary and unavoidable. This thesis, the first of its kind in Lebanon and the Middle East, undergoes a pragmatic randomised controlled trial in Lebanon’s only public psychiatry hospital. I begin with systematically defining ‘what is aggression’ specifically within the psychiatry emergency setting and the common disorders associated with it. I then conducted a systematic literature review of all known surveys examining both clinicians’ opinions and practice on how aggressive episodes are treated. Following the survey of surveys, I proceeded to conduct a survey of both clinicians’ opinions and what happens in practice in Lebanon’s Psychiatric Hospital of the Cross. With the results and assistance from Cochrane Library, I conducted a systematic overview and updated reviews - both direct and indirect. While results did show a variety of treatments used in Lebanon have been tested in trials, Lebanon’s main SOS treatment – the ‘HPC’ treatment has never been investigated within a trial and no reviews exist, although there is evidence it is used in practice. With this, I designed the trial protocol suited for Lebanese practice and with the University of Nottingham’s ethics board and representatives of the Lebanese hospital, the trial commenced and ran to completion over a period of 10 months. A total of 100 patients were randomised with 48 in the HP group and 52 in the HPC group. Primary measures of outcomes were calm or tranquil at 20 minutes. Results showed no significant differences between both interventions with confidence intervals showing a slight preference towards the triple therapy when sampling size is adjusted. The thesis concludes with the difficulties of running such a trial within the region and the practical solutions to each problem presented.